ROLE PLAYED AND CONSTRAINTS FACED BY FISHER WOMEN IN INLAND FISH MARKETING IN ANAND GUJARAT - PANIGRAHY, SHAKTI RANJAN; VAHONIYA, DILIP (Journal of the Inland Fisheries Society of India, 2021)
Fifty female retailers were selected from different markets of Anand, Gujarat district and responses had been captured through a pretested structured schedule. During analysis, it was found that fisher women were mainly doing segregation, cleaning and collection of cash after selling of the produce whereas selling of fish had been handled by both male and female fishers of the district. During selling of fresh fish, female retailers were facing much real cost and increase infrastructural set up may enhance their retaining and bargaining power. Female retailers may be empowered by proving training in their respective areas. Key words: Real cost, Fish marketing, Fishery Activities